A Review of Central Venous Access Using Ultrasound Guidance Technology. (April 2020) - Crenshaw, Nichole A.; Briones, Patricia; Gonzalez, Juan M.; Ortega, Johis
Abstract : More than 5 million central lines are placed in the United States each year. Advanced practice providers place central lines and must understand the importance of ultrasound guidance technology. The use of anatomic landmarks to place central lines has been employed in the past and in some instances is still used. This method may make accessing the target vessel difficult in the patient with anomalous anatomy or in the obese patient. These characteristics decrease successful placement and increase complications. Different organizations have agreed that the use of ultrasound during central venous access has decreased rates of complication and cost. In addition to cannulating and accessing a central vein, ultrasound can be used to rapidly confirm placement and to rule out complications such as pneumothorax. Utilizing ultrasound to assist in performance of procedures, and in assessment of patients, is a skill that should be optimized by nurse practitioners.